2022
DOI: 10.3390/buildings12101508
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Indicators of Sustainable Campus Renewal and Reconstruction in Pursuit of Continuous Historical and Regional Context

Abstract: As cities transition from incremental development to stock development, university campuses in suburban areas are progressively becoming urban university campuses. The stability of the boundary between urban university campuses and the city, along with the fact that the campus’s overall spatial capacity is reaching its maximum, makes it impossible for urban university campuses to have future spatial expansions. This article focused on the stock development, renewal, and transformation of urban campuses. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The present study extends our previous suggestions for human-centric campus planning [24,25]. The rubric in planning university campuses is more manageable than the entire city since it sets limits of function and region [26,27]. It is the paradigmatic example of a pedestrian environment, except when the institution is situated in a city center.…”
Section: Two Contrasting Philosophies For Campus Designsupporting
confidence: 70%
“…The present study extends our previous suggestions for human-centric campus planning [24,25]. The rubric in planning university campuses is more manageable than the entire city since it sets limits of function and region [26,27]. It is the paradigmatic example of a pedestrian environment, except when the institution is situated in a city center.…”
Section: Two Contrasting Philosophies For Campus Designsupporting
confidence: 70%
“…Previous The research also shows that historical buildings in campus common spaces can facilitate the free activities of college students, such as walking, playing and picture-taking, and have a positive impact on emotions and restoration from stress. This is consistent with the research results of Weber, Masullo, Reece and Guo, which revealed that architectural environments with a strong historical and cultural atmosphere are conducive to enhancing people's spatial experiences and promoting psychological restoration (22)(23)(24)(25).…”
Section: Influence Paths and Effects Of The Characteristics Of The Ar...supporting
confidence: 92%
“…Based on machine learning simulation, Xiang et al concluded that the shape and layout of building enclosures in common spaces are significantly related to people's emotions (20). Lindal, Weber and Masullo et al believed that the number of turns in architectural outlines and historical elements in the architectural environment, and rich changes in building facades, can arouse people's interest and divert their attention from their daily needs and spiritual content and help them to achieve psychological restoration (21)(22)(23)(24)(25)(26). In addition, there is ample evidence that increases in the quantity, type and color of vegetation in campus landscape spaces and sports fields is significantly related to enhanced psychological restoration (27)(28)(29).…”
Section: Characteristics Of Campus Common Spacesmentioning
confidence: 99%
“…Fifth, we considered only the environmental characteristics of UPGS, and certain external environmental characteristics can also seriously affect UPGS quality. Further research should integrate key external environmental features and further revise the Huff-2SFCA model (Guo et al, 2022;Zhao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%